Technology Training and Empowerment for the Visually Impaired: Kenya Perspective - Were, Charles Michael (Advances in Social Sciences Research Journal, 2021)
A key goal of education for any country is to make sure that every pupil has a chance to excel, both in school and life. Increasingly, a child’s success in school will determine his success as an adult; will determine whether he/she goes to college, what profession that he/she enters and how much they are paid. Kenya’s education system has laid emphasis on a cluster of science subjects that must be passed for one to be placed in a meaningful course at tertiary level, university and finally employment. The Visually impaired child has been disadvantaged and this study therefore tried to investigate why there are more street beggars who are Visually impaired as compared to other persons with disabilities in the Kenyan major towns. The study was conducted in the three towns within Kenya, namely: Kisumu, Nakuru and Nairobi. The study population was 145, and a purposive sampling was used to select the 60 respondents. The study found that the Visually impaired persons who were beggars on the street had basic education at primary level and some had form four certificate, however they had failed to gain any meaningful employment due to the growing need of technology in the work place and the increasing interest in the role of information and communication technologies for one to be employed. The study also found that as much as there is an increasing effort by the Government to have computer studies for all schools in Kenya. The Jaw’s programme is lacking in those computers and therefore the visually impaired learners have not had an access to computer education and hence the mass influx of beggars. The study recommends that of the schools where the Visually impaired learners are in inclusive education, there should be at least two computers with a Jaw programme to help the Visually impaired have an access in computer literacy and hence employment opportunity. The study also recommends that the street beggars with form four educations should be given vocational training with information technology so as to empower them with the current basic skills to compete favourable with other job seekers.